Viruses and exacerbations of chronic obstructive pulmonary disease: unmet clinical need - L. Buss (Journal of Virus Eradication, 2015)
Chronic obstructive pulmonary disease (COPD) is a non-communicable long-term condition characterised by accelerated lung-function decline and intermittent episodes of respiratory illness called exacerbations. We discuss the current understanding of the role of viruses in these elements of COPD. The burden of acute viral illness in COPD is great and largely unrecognised. Because naturally occurring exacerbations are inherently difficult to study, only recently have we understood underlying pathophysiological mechanisms and the true prevalence of viral exacerbations. Data are also emerging to support a potential role for chronic viral infection in the progression of stable COPD. As knowledge in these two areas develops, it is clear that the role of viruses in COPD represents a significant unmet clinical need.